The prognostic importance of the global immune-nutrition-information index (GINI) in patients with Ras wild type metastatic colorectal cancer - Oktay Bozkurt; Rıdvan Gönül; Bugra Umut Kaya; Gozde Erturk Zararsiz; Mevlüde İnanc; Metin Özkan (Scientific Reports)
Abstract In this study, we aimed to evaluate the clinical impact of the Global Immune-Nutrition Information Index (GINI) in patients with Ras wild-type metastatic colorectal cancer (mCRC) who received first-line palliative chemotherapy Ras wild-type mCRC. We retrospectively reviewed 177 patients diagnosed with Ras Wild Type mCRC between March 2009 and December 2023. The GINI was defined as follows: GINI= [C-reactive protein×platelet×monocyte×neutrophil]/[albumin×lymphocyte]. According to threshold values determined by receiver operating characteristics (ROC) analysis, the GINI was divided into two groups with < 2000 and ≥ 2000. Survival probabilities were predicted with the Kaplan-Meier method and group comparisons were applied with the Log-rank test. Furthermore, univariate and multiple Cox regression analyses were used to determine the most substantial risk elements. Median progression-free survival (PFS) 15 months in the group with GINI ≥ 2000 (95% Confidence interval (CI): 10.5–19.48) and 27 months (95% CI: 17.5–36.4) in the group with GINI < 2000 (p = 0.00021). The median OS was 27 months (95% CI: 23.8–30.1) in the GINI ≥ 2000 group and 77 months (95% CI: 59.7–94.2) in the GINI < 2000 group (p < 0.001). The results of multivariate analysis for PFS showed that albumin (HR, 1.83, p = 0.009), and prechemotherapy GINI (HR 1.79, p = 0.004) were significant independent prognostic factors. The results of multivariate analysis for OS showed that performance status (HR, 1.65; p = 0.018), number of metastatic sites (HR, 1.74, 0.005), skin toxicity (HR, 1.79, p = 0.003), pre-chemotherapy NLR (HR, 1.49, p = 0.045) and prechemotherapy GINI (HR 3.25, p < 0.001) were significant independent prognostic factors. Higher GINI values were associated with worse survival outcomes in patients with RAS wild-type mCRC, supporting its potential clinical use as a prognostic biomarker.